Social work: theory and practice with the system approach - Irina Savelchuk (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
The article is a critical analysis of the main provisions of a systematic approach to the theory and practice of social work. Proved that the characteristics of social work, its effectiveness and success defined systemic integrity. Solved means of implementing a systematic approach to the content of social work with different groups of clients.